RUPTUR ANEURISMA SINUS VALSAVA (RSOVA) PADA WANITA MUDA: LAPORAN KASUS: RUPTUR SINUS OF VALSAVA ANEURISMA (RSOVA) IN YOUNG WOMAN: A CASE REPORT - Salsa, Siti Tari; Saragih, Yusrina (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Sinus of Valsalva aneurysm (SOVA) is a rare cardiac condition that includes an abnormal dilatation of the aortic root between the aortic valve annulus and the sinotubular junction caused by weakness in the elastic lamina at the junction of the aortic media and the annulus fibrosus. Usually, the sinuses prevent the coronary artery ostia occlusion during systole when the aortic valve opens. The normal sinus diameter is less than 4 cm for men and 3.6 cm for women. A 28 years old woman admitted to ambulatory clinic with chief complaint progressive dyspnea on exertion and exercise intolerance in a month .Physical examination found with ascites, bilateral pitting edema, continuous murmur at the lower left sternal border, crackles in lower lung area . Chest x-ray showed cardiomegaly with increase vascularisation, whereas electrocardiography showed sinus tachycardia with right axis deviation. Transthoracic echocardiography (TTE) showed a ruptur sinus valsalva opposite from Right Coronary Cuspid (RCC of Aorta Valve) toward to RVOT with diameter 16 mm, gradient 72 mmHg, got confirmed by Transesophageal echocardiography (TEE) AbstrakAneurisma sinus Valsava (SOVA) adalah kondisi jantung langka yang meliputi dilatasi abnormal akar aorta antara anulus katup aorta dan sambungan sinotubular yang disebabkan oleh kelemahan lamina elastis pada sambungan media aorta dan anulus fibrosus. Biasanya, sinus mencegah oklusi ostium arteri koroner pada saat sistol ketika katup aorta terbuka. Diameter sinus normal kurang dari 4 cm untuk pria dan 3,6 cm untuk wanita. perempuan berusia 28 tahun datang ke klinik rawat jalan dengan keluhan utama sesak napas progresif saat aktivitas dan intoleransi olahraga selama satu bulan. Pemeriksaan fisik menemukan ascites, edema pitting bilateral, murmur kontinu di batas sternal kiri bawah, dan krepitasi di area basal paru. Foto toraks menunjukkan kardiomegali dengan peningkatan vaskularisasi, sedangkan elektrokardiografi menunjukkan sinus takikardia dengan deviasi aksis kanan. Ekokardiografi transtorasik (TTE) menunjukkan ruptur sinus valsalva yang berlawanan dari *Right Coronary Cuspid* (RCC katup aorta) menuju *RVOT* dengan diameter 16 mm dan gradien 72 mmHg, yang kemudian dikonfirmasi dengan ekokardiografi transesofageal (TEE).